The impact of external debt, remittances, political stability, and urbanization on renewable energy consumption in BIMSTEC nations: Evidence from DCE and DCE-IV estimation - Qamruzzaman, Md (International Journal of Renewable Energy Development, 2025)
This study delves into the intricate relationships among external debt, remittances, political stability, urbanization, and renewable energy consumption in the context of BIMSTEC nations for 1995-2021. Motivated by the growing significance of sustainable energy practices and the need for informed policy decisions. This research employs a comprehensive methodology, including recently introduced Cross-sectional dependency, Slope of heterogeneity test, error correction-based cointegration test, Dynamic Common Correlated Effects (DCE), and instrumental variable-adjusted DCE method. While external debt shows a positive association with renewable energy consumption, careful consideration is required, as indicated by the nuanced impact of the DCE and Instrumental Variable (DCE-IV) models. Remittances exhibit a positive nexus with renewable energy consumption, emphasizing the role of household purchasing power. Urbanization, reflecting a positive correlation with unemployment rates, surprisingly points towards an increased demand for renewable energy, highlighting the need for strategic planning. Political stability, trade openness, and foreign direct investment (FDI) also demonstrate varying impacts on renewable energy consumption. The findings underscore the intricate nature of these relationships, urging policymakers to adopt tailored approaches. Consequently, this study contributes valuable policy insights for BIMSTEC nations, emphasizing the importance of sustainable energy strategies aligned with economic and social dynamics.